Effects of dietary Clostridium butyricum on the growth performance, digestion, and intestinal health of spotted sea bass (Lateolabrax maculatus) - Kong, Lumin; Ma, Jianrong; Zhou, Sishun; Lin, Hao; Long, Zhongying; Qin, Huihui; Liu, Longhui; Lin, Yi; Huang, Zhangfan; Li, Zhongbao (Frontiers in Immunology, 2023)
Clostridium butyricum (CB) is known to promote growth, enhance immunity, promote digestion and improve intestinal health. In this study, we investigated the effects of CB in the feed on growth performance, digestion and intestinal health of juvenile spotted sea bass. To provide a theoretical basis for the development and application of CB in the feed of spotted sea bass, a total of 450 spotted sea bass with initial body weight of (9.58±0.05) g were randomly divided into 6 groups. Gradient levels with 0, 0.1%, 0.2%, 0.3%, 0.4% and 0.5% of CB (1×10 9 cfu/g) were supplemented into diets, designating as CC, CB1, CB2, CB3, CB4 and CB5, respectively. Each group were fed for 54 days. Our results suggested that dietary 0.2% and 0.3% of CB can significantly increase the weight gain (WG) and specific growth rate (SGR) of spotted sea bass. The addition of CB significantly increased intestinal amylase activity, intestinal villus length, intestinal villus width, and intestinal muscle thickness.Similarly, CB supplementation increased the expression of tumor necrosis factor-α (TNF-α) and interleukin-8 (IL-8). Sequence analysis of the bacterial 16S rDNA region showed that dietary CB altered the intestinal microbiota profile of juvenile spotted sea bass, increasing the dominant bacteria in the intestinal, decreasing the harmful bacteria. Overall, Dietary addition of CB can improve the growth performance, enhance intestinal immunity, improve intestinal flora structure, and comprehensively improve the health level of spotted sea bass.